Tissue Testing and Interpretation for Florida Turfgrasses - Travis W. Shaddox; Jerry B. Sartain (EDIS)
Tissue analysis offers a precise estimate of a plant’s nutritional status at the time of sampling. Nutrient deficiencies can be detected with tissue analysis before visual symptoms appear. This revised 3-page fact sheet describes the importance of tissue testing and how to interpret the results. Written by T. W. Shaddox and published by the Environmental Horticulture Department, March 2017.